Pendampingan Hadroh Al-Banjari Untuk Meningkatkan Semangat Berselawat Pada Masa Pandemi: Hadroh Al-Banjari's Assistance to Improve The Spirit of Saving in Pandemic Times - Dhea Nanda Listiani; Farida Yufarlina Rosita (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Al-Banjari is an Islamic art originating from Kalimantan. Until now, there are still many teenagers who really love this art because of its stomping, dynamic, and varied rhythm. Musala An-Nur is one of the service partners who have the Al-Banjari hadroh group. However, Al-Banjari hadroh training activities at that place could not be carried out properly as usual during the pandemic and the PPKM rules. However, the children's enthusiasm for practice did not wane in the slightest. For this reason, the mentoring activity for Al-Banjari hadroh activities is carried out so that hadroh exercises can still be carried out. Based on these assets, the Asset-Based Community Development (ABCD) approach is applied in this service activity. The results achieved after carrying out this mentoring are that children in the Musala An-Nur environment can carry out hadroh exercises as usual and can develop their creativity in playing the Al-Banjari hadroh instrument. In addition, Al-Banjari hadroh activities can also increase the spirit of prayer during the pandemic. The selawat which is sung in the Al-Banjari hadroh activity is expected to be able to fill free time with positive activities. Al-Banjari merupakan sebuah kesenian Islami yang berasal dari Kalimantan. Sampai sekarang ini, masih banyak remaja yang sangat menggandrungi kesenian ini karena iramanya yang menghentak, rancak, dan variatif. Musala An-Nur merupakan salah satu mitra pengabdian yang memiliki grup hadroh Al-Banjari. Akan tetapi, kegiatan latihan hadroh Al-Banjari di tempat tersebut tidak dapat terlaksana dengan baik sebagai mana biasanya selama pandemi dan adanya aturan PPKM. Walaupun demikian, semangat anak-anak untuk berlatih tidak memudar sedikitpun. Untuk itu, kegiatan pendampingan kegiatan hadroh Al-Banjari ini dilakukan agar latihan hadroh tetap bisa terlaksana. Berdasarkan aset tersebut, pendekatan Asset-Based Community Development (ABCD) diterapkan dalam kegiatan pengabdian ini. Hasil yang dicapai setelah melaksanakan pendampingan ini adalah anak-anak di lingkungan Musala An-Nur dapat melaksanakan latihan hadroh sebagai mana biasanya dan bisa mengembangkan kreativitasnya dalam memainkan alat hadroh Al-Banjari. Selain itu, kegiatan hadroh Al-Banjari juga dapat meningkatkan semangat berselawat pada masa pandemi. Selawat yang dilantunkan dalam kegiatan hadroh Al-Banjari ini diharapkan dapat mengisi waktu luang dengan kegiatan positif.